Up in the air [videorecording (DVD)] - Reitman, Jason, 1977-; Reitman, Jason, 1977-; Reitman, Jason, 1977-; Clooney, George; Farmiga, Vera; Kendrick, Anna; Bateman, Jason; McBride, Danny, 1976-; Lynskey, Melanie; Simmons, J. K.; Elliott, Sam, 1944-; Kirn, Walter, 1962- (Paramount Home Entertainment, 2010)
Ryan Bingham is a corporate downsizing expert who flies all over the world on business. Just as he is on the cusp of reaching ten million frequent flyer miles, and meeting the frequent traveler woman of his dreams, his company grounds him. When Bingham goes on his last cross country firing expedition, he will learn that life isn't about the journey, but about the connections made along the way.